Diarrhea as an Early and Predominant Manifestation of Coronavirus Disease 2019 (COVID-19): A Case Report - Nikko Darnindro; Linda Nurdewati; Annela Manurung; M Ikhsan Mokoagow; Jerry Nasarudin; Elisabeth Yasmine Wardoyo; Anggraini Permata Sari; Aryan Yohanes Djojo; Martha Iskandar; Giri Adji; Marina Epriliawati; Ifael Mauleti; et al. (Acta Medica Indonesiana)
Coronavirus disease 2019 (COVID-19) is a new infectious disease that spreads very rapidly and therefore, WHO has declared it as a global pandemic disease. The main clinical symptoms found in COVID-19 patients are cough and fever; however, in some cases, diarrhea can be one of the early symptoms. The present case report describes a patient who came with a complaint of diarrhea without fever and she was later confirmed to be positive for COVID-19 during hospitalization. The presence of unspecified initial symptoms calls for greater vigilance from health workers in establishing diagnosis patients with COVID-19.